The influence of Digitalisation on Strategic Agility of a South African Mining Company - Mosena, Nthabiseng Nicolene (University of the Witwatersrand, Johannesburg, 2023)
A profound transformation in the way economic activities are perceived and controlled is currently unfolding. This transformation is primarily propelled by the advent of a flexible technological platform that serves as the foundation for the development of new business value chains and ecosystems. Digitalisation, which acts as the gateway to accessing this state-of-the-art infrastructure, carries profound implications for how organisations strategically evolve in response to changing environmental factors. Strategic agility has increasingly become a central factor in ensuring business survival within this context. While digitalization is an undeniable reality for businesses and plays a role in generating value, few studies have examined its impact on strategic agility and thus improving organisational performance in the mining sector. The role of digitalisation as a facilitator of strategic agility has sparked debates and discussions among scholars and industry professionals. Although some research indicates that digitalisation is the foundation of strategic agility, other perspectives dispute this assertion. Recognizing this disparity, the primary aim of this research was to investigate the relationship between digitalisation and strategic agility. In order to draw conclusions regarding this observed relationship, primary data was collected from individuals at the management level within a South African company, which was then meticulously prepared and analysed. The analysis was conducted using quantitativedata analysis. The study found that digitalisation empowers organisations with the tools, insights, and capabilities to enhance their strategic agility. By leveraging digital technologies, organisations can sense and respond to changes rapidly, make data-driven decisions, streamline operations, innovate, and deliver superior customer experiences. Embracing digitalisation has become essential for organisations to thrive in today's fast-paced and highly competitive landscape. After conducting an extensive examination, this research establishes that digitalization is positively associated with strategic agility and that collectively the variables are important predictors of organisational performance. The study concludes that organizations should adopt an iterative approach to digitalization, with clarity of purpose, strategically in order to efficiently attain control over their intended impact on strategic agility
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Digitalisation; Strategic Agility; Strategy; Organisational Performance; UCTD; SDG-9: Industry, innovation and infrastructure